Avaliação dos efeitos sistêmicos induzidos por uma fosfolipase A2 isolada da peçonha da serpente Bothrops moojeni - Costa, Kellen Cristina Torres (2017)
Snakes venom is considered the most complex venom of the animal kingdom with a great mixture of components and toxic properties. Within this group of organic and inorganic compounds are the phospholipases A2 (PLA2s), a superfamily of enzymes that catalyzes the hydrolysis of phospholipids releasing several products according to the site of action on the substrate. Due to great clinical interest, several studies have portrayed the structural and functional characterization of PLA2s isolated from the venom of bothropic snakes. The present work aimed to describe the purification of a PLA2 isolated from Bothrops moojeni, called BmooTX-I, and evaluate evaluate the enzyme-induced systemic effects in experimental animals.. The toxin was purified using size ion-exchange (DEAE-Sephacel) and molecular exclusion (Sephadex G-75) columns. SDS-PAGE showed that BmooTX-I has an apparent molecular mass of 15 kDa. Its catalytic activity was significantly high when compared to the crude venom of B. moojeni. BmooTX-I altered physical-chemical parameters in the urine of animals and also caused important systemic changes related to the liver, muscle, kidneys and pancreas. Therefore, this work can contribute greatly to the medical-scientific area since it aggregates information for possible discoveries of more specific therapies for bothropic acidentes, and also, because phospholipases A2 are directly related to various pathologies.